Generation of Pseudomonas mutants for investigating a model mixed species biofilm - Neo, Desmond (2018)
Mixed-species microbial biofilms are the predominant form of biofilms in nature, however, majority of studies on biofilms have focused on single-species biofilms. Unique interspecies interactions could shape the biofilm community structure and functions in a manner that is not represented in single-species biofilms. Thus, a model mixed-species biofilm comprised of Klebsiella pneumoniae (KP-1), Pseudomonas aeruginosa (PAO1) and Pseudomonas protegens (Pf-5) was selected to investigate the differentially expressed genes between single-species and mixed-species biofilms to identify key genes within Pf-5 involved in overall biofilm structure via mutagenesis studies. This study involved the fluorescent tagging of PAO1 via specific insertion mutagenesis involving a Tn7 transposon. Deletion mutagenesis of differentially expressed genes in Pf-5 were performed, with PFL_5251 as the target gene to develop a reliable method for deletion mutagenesis in Pf-5 where multiple key methods were identified at each stage. Both electroporation and conjugation were evaluated for the introduction of pK18 assembled with deletion construct into Pf-5. Both failed to select for transformants and transconjugants until the antibiotic concentrations were optimized. PFL_5251 mutants were generated and confirmed for Pf-5 via sequence alignment. This paved the way for further analysis with bioimaging techniques to help improve understanding and determination of genes important in mixed-species biofilms.